2021
DOI: 10.1088/1755-1315/912/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and screening of local cellulolytic fungi from the digestive tract larvae of Oryctes rhinoceros L., North Sumatra

Abstract: Cellulose, which is the main component of plant cell walls from higher plants, has been studied from different aspects. It is insoluble in a wide variety of solvents and is resistant to various chemicals treatments. Fungi are a group of cellulose-degrading microbes and plays major role in recycling of lignocellulosic material in nature. This study aimed to obtain cellulolytic fungi from the digestive tract of Oryctes rhinoceros L. larvae and to determine cellulolytic activity. Isolation and screening of cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Fusarium culmorum and Penicillium crustosum [3]. Eleven cellulolytic fungi have been isolated from the digestive tract of O. rhinoceros larvae which showed their potential ability based on the qualitative results [4]. Based on a study by Goyari et al [5], three isolates of cellulolytic fungi were isolated from forest soil showed the highest cellulolytic activity and FPase activity, based on the molecular identification of 3 cellulolytic isolates classified in Talaromyces verruculosus, Trichoderma gamsii and Trichoderma atroviride.…”
Section: Introductionmentioning
confidence: 99%
“…Fusarium culmorum and Penicillium crustosum [3]. Eleven cellulolytic fungi have been isolated from the digestive tract of O. rhinoceros larvae which showed their potential ability based on the qualitative results [4]. Based on a study by Goyari et al [5], three isolates of cellulolytic fungi were isolated from forest soil showed the highest cellulolytic activity and FPase activity, based on the molecular identification of 3 cellulolytic isolates classified in Talaromyces verruculosus, Trichoderma gamsii and Trichoderma atroviride.…”
Section: Introductionmentioning
confidence: 99%